Perilaku Mahasiswa Dalam Menonton Tayangan Channel Youtobe Cretivox (Studi Deskriptif Pada Mahasiswa Ilmu Komunikasi Universitas Singaperbangsa Karawang) - Kristofer Sahala Tua Butar Butar; Firdaus Yuni Dharta; Dadan Kurniansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Youtube users in Indonesia are very numerous and have different tastes in choosing shows, even this has created a lot of very diverse content on YouTube, ranging from music videos, parody videos, culinary videos, short films, mystical shows, film reviews, video blogs and Social Experiments. . Currently there are several Youtube channels that focus on Social Experiment content, one of which is Cretivox.In this study using qualitative methods and descriptive approach. The theory used in this study is the Cultivation Theory proposed by George Gebner. Data collection techniques were carried out by interviews, non-participant observation and documentation.The results showed that the changes in behavior obtained by the informants in watching Cretivox Youtube channel broadcasts were very diverse, starting from being aware that everyone's opinions, ways of thinking and behavior varied, respecting other people's opinions more and understanding other points of view more, opening perspectives on other things. , better understanding of behavior when faced with things that have never been experienced The motives of the informants in watching Cretivox Youtube channel broadcasts are also in line with the cultivation theory concerning the impact of watching on social reality in shows regarding individual perceptions, attitudes and values